Human-wildlife conflict in Chiredzi Gonarezhou National Park: Conflict to coexistence - Basera, Vitalis; Godfrey, Makandwa (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
The successful conservation of wildlife and the well-being of communities living adjacent to protected areas largely depends on the extent to which the communities and wildlife themselves can coexist. Where coexistence fails, human-wildlife conflicts (HWC) arise. Almost every country in the world faces some form of HWC, and highly biodiversity, developing countries like Zimbabwe particularly struggle with this issue. The purpose of this study was to provide the detailed information on the status, nature and dynamics of HWC, how it is experienced and how communities living in and adjacent to HWC hotspots around Gonarezhou are affected. Knowledge gained from this study will inform the design and implementation of a suite of strategies and interventions in HWC mitigation. This study was conducted in eight wards with HWC hotspots around Gonarezhou in Zimbabwe Zimbabwe in particular Chitsa, Chibwedziva, Twanani, Batanai, Chichingwe, Xibhavahlengwe, Sengwe and Xini. The local communities in these study sites live alongside and share their space with wildlife. A mixed methods approach was used to conduct this study, which involved the use of quantitative and qualitative data collection techniques. The quantitative data collection involved the use of structured household questionnaires, and a total of 560 households were interviewed across the study sites. The qualitative data collection techniques involved discussions with 28 focus groups and 12 interviews with key informants across the eight study sites. Results from household surveys showed that attitudes towards wildlife protection are generally positive. The incidences of HWC varied across the study sites with some sites such as Sengwe and Xibhavahlengwe experiencing higher levels of conflict. The study recommends for a holistic solution which addresses both HWC and poverty is critical in protecting biodiversity and improving livelihoods in communities around Gonarezhou National Park.